2018
DOI: 10.1021/acs.jpclett.8b01333
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Complex Effects of H2O on Discharge–Recharge Behaviors of Aprotic Lithium–O2 Batteries

Abstract: The addition of HO, even trace amount, in aprotic Li-O batteries has a remarkable impact on achieving high capacity by triggering solution mechanism, and even reducing charge overpotential. However, the critical role of HO in promoting solution mechanism still lacks persuasive spectroscopic evidence, moreover, the origin of low polarization remains incompletely understood. Herein, by in situ spectroscopic identification of reaction intermediates, we directly verify that HO additive is able to alter oxygen redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 42 publications
5
61
0
Order By: Relevance
“…Li + is exchanged with H + in LiO 2 and Li 2 O 2 , forming soluble intermediates (Scheme b) . Aetukuri et al.…”
Section: Redox Mediators For Dischargesupporting
confidence: 82%
“…Li + is exchanged with H + in LiO 2 and Li 2 O 2 , forming soluble intermediates (Scheme b) . Aetukuri et al.…”
Section: Redox Mediators For Dischargesupporting
confidence: 82%
“…The cell with BA exhibited larger discharge capacity and higher coulombic efficiency, which is probably due to a small amount of water produced by reactions and (2). It has been reported that small amount of water has such positive effects in LOBs . SEM, X‐ray diffraction (XRD), and X‐ray photoelectron spectroscopy (XPS) results show that the discharge product is always Li 2 O 2 particles, which are oxidized after charge (Figures S3 and S5, Supporting Information).…”
mentioning
confidence: 99%
“…In contrast to conventional Li–O 2 batteries, which work via Li 2 O 2 formation, a novel Li–O 2 battery employing LiOH as the energy carrier has attracted extensive interest . The Li–O 2 battery that works via LiOH formation, 4Li + 2H 2 O + O 2 ⇌ 4LiOH ( E ° = 3.32 V), delivers a low charge potential and high cycling stability because of the enhanced conductivity of LiOH and the alleviation of side reactions caused by the high nucleophilicity of Li 2 O 2 . Additives such as H 2 O and lithium iodide (LiI) greatly impact the conversion of the aforementioned Li–O 2 batteries, acting as either initiators or catalysts to promote the formation of LiOH .…”
Section: Other Energy Carriersmentioning
confidence: 99%
“…Unfortunately, humidity can also limit the cycling ability and rate performance because of its negative effect on Li 2 O 2 /O 2 conversion . In the case of Li–O 2 batteries with H 2 O, the discharge products can be Li 2 O 2 and/or LiOH, depending on the catalysts, electrolytes and H 2 O concentration. Li et al studied the mechanism of water catalysis based on the Ru/MnO 2 /SP cathode of Li–O 2 batteries.…”
Section: Other Energy Carriersmentioning
confidence: 99%
See 1 more Smart Citation